Irrigated Sunflowers in Northwest Kansas: Productivity and Canopy Formation - F. Lamm; R. M. Aiken; A. A. AbouKheira; G. J. Seiler (Kansas Agricultural Experiment Station Research Reports, 2017)
Sunflower was grown in a three-year study (2009, 2010, and 2012) at the Kansas State University Northwest Research-Extension Center at Colby, KS, under a lateral move sprinkler irrigation system. Irrigation capacities were limited to no more than 1 inch every 4, 8, or 12 days but were scheduled only as needed as determined with a weather-based water budget. Achene (sunflower seed) yields and oil yield generally plateaued at the medium irrigation level. Dormant preseason irrigation increased achene yield and oil yield by 2% with most of this increase occurring in the extreme drought year, 2012. The optimum harvest plant population for sunflower in this study in terms of achene yield and oil yield was approximately 19,000 to 20,000 plants/a.
Keywords: sunflower; irrigation; canopy